A 26 year physiological description of a National Hockey League team - Quinney, H. A.; Dewart, R.; Game, A.; Snydmiller, G.; Warburton, D.; Bell, G. (Applied Physiology, Nutrition, and Metabolism, 2008)
The primary purpose of this investigation was to examine the physiological profile of a National Hockey League (NHL) team over a period of 26 years. All measurements were made at a similar time of year (pre-season) in 703 male (mean age ± SD = 24 ± 4 y) hockey players. The data were analyzed across years, between positions (defensemen, forwards, and goaltenders), and between what were deemed successful and non-successful years using a combination of points acquired during the season and play-off success. Most anthropometric (height, mass, and BMI) and physiological parameters (absolute and relative VO2 peak, relative peak 5 s power output, abdominal endurance, and combined grip strength) showed a gradual increase over the 26 year period. Defensemen were taller and heavier, had higher absolute VO2 peak, and had greater combined grip strength than forwards and goaltenders. Forwards were younger and had higher values for relative VO2 peak. Goaltenders were shorter, had less body mass, a higher sum of skinfolds, lower VO2 peak, and better flexibility. The overall pre-season fitness profile was not related to team success. In conclusion, this study revealed that the fitness profile for a professional NHL ice-hockey team exhibited increases in player size and anaerobic and aerobic fitness parameters over a 26 year period that differed by position. However, this evolution of physiological profile did not necessarily translate into team success in this particular NHL franchise.